2022
DOI: 10.1007/s12015-022-10369-1
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Overview of Global Trends in MSC-Based Cell Therapy

Abstract: Human mesenchymal stem cells (MSCs), also known as mesenchymal stromal cells or medicinal signaling cells, are important adult stem cells for regenerative medicine, largely due to their regenerative characteristics such as self-renewal, secretion of trophic factors, and the capability of inducing mesenchymal cell lineages. MSCs also possess homing and trophic properties modulating immune system, influencing microenvironment around damaged tissues and enhancing tissue repair, thus offering a broad perspective i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(73 citation statements)
references
References 194 publications
0
73
0
Order By: Relevance
“…Hospital Essen, University of Duisburg-Essen, Essen, Germany. 3 National University of Ireland Galway, Galway, Ireland. 4 LUMC, Sequencing Analysis Support Core, Leiden, The Netherlands.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospital Essen, University of Duisburg-Essen, Essen, Germany. 3 National University of Ireland Galway, Galway, Ireland. 4 LUMC, Sequencing Analysis Support Core, Leiden, The Netherlands.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…The lack of effective treatments for inflammatory diseases as well as major age-related diseases, e.g., chronic Inflammatory Bowel Disease, neurodegenerative disease and osteoarthritis, imposes a huge economic burden on individual patients and health care systems [1,2]. In that respect, caretakers have high hopes for the application of cell therapy in the clinic using human adult mesenchymal stromal cells (hMSCs) [3]. Upon exposure to signals associated with the in vivo injured environment hMSCs are known to respond with a process named licensing.…”
Section: Introductionmentioning
confidence: 99%
“…How MSCs fit into the landscape of regenerative medicine: The connection to very small embryonic-like stem cells Unlike hES and iPS cells, MSCs have entered the clinics, and have shown abundant promise (Jovic et al, 2022). As we recently discussed (Bhartiya et al, 2022a), the beneficial effects of transplanting MSCs, as reported in multiple clinical trials (Squillaro et al, 2016;Esfandyari et al, 2020), come from their capacity to rejuvenate (i.e., improve the microenvironment/niche of) diseased tissues by providing paracrine support to the tissue-resident, endogenous very small embryonic-like stem cells (VSELs), which in turn regenerate the diseased tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, despite enhanced tissue repair and functioning after MSCs therapy, the studies have not found significant evidence for the differentiation of MSCs into other cell types. Therefore, the prevailing view now is that MSCs perform their therapeutic actions via paracrine mechanisms rather than by direct differentiation and cell replacement (20,21). One of the paracrine effects of MSCs is modulation of the immune system.…”
Section: Introductionmentioning
confidence: 99%